(untitled) (International Journal of Engineering and Computer Science, 2013)
- In the last few decades with the rapid improvement in the field of computer technology, data and communication the concept of “GRID COMPUTING” have become more prominent. The popularity of the Internet and availability of high-speed networks have gradually changed the way we do computing. These technologies have enabled the cooperative use of a wide variety of geographically distributed resources as a single more powerful computer. This new method of pooling resources for solving large-scale problems is called as grid computing. The concept of grid computing have not only evolved in terms of topology but have also included wide spread data communication by the means of resource-sharing, however it is still lacking in terms of trust and reliability. Since a major ratio of people are communicating and sharing data which thereby decreases the trust of the users. It has not able to convince the user fully. This paper describes the concepts underlying grid computing and the trust model on which the reliability factor totally depends